Odpowiedź:
a)
Obw = 1/3a + 1/3a + (a - 1/3a) + 3/4b + a + b
= 1/3a + 1/3a + a - 1/3a + 3/4b + a + b =
= 2 1/3a + 1 3/4b
P1 = 1/3a^2 = 1/9a2
P2 = 3/4b • a = 3/4ab
Pc = 1/9a2 + 3/4ab
b)
Obw = 2a + 6b + 2ab
P1 = ab
P2 = ab
P3 = ab • ab = a2b2
Pc = ab + ab + a2b2 = a2b2 + 2ab
c)
Obw = 4x + 4y
Pc = xy • xy = x2y2
d)
Obw = 3 + 5 + 2a + 2a + a + a + 8 - (2 + a) + a + 2 + 2a + 5 = 8 + 6a + 8 - 2 - a + 3a + 7 =
= 8a + 21
P1 = a2
P2 = a • 2a = 2a2
P3 = 2a
P4 = 3 (5 + a) = 3a + 15
Pc = a2 + 2a2 + 2a + 3a + 15 =
= 3a2 + 5a + 15
Szczegółowe wyjaśnienie: